The Use of Polymer Blends in the Treatment of Ocular Diseases - Raquel Gregorio Arribada; Francine Behar-Cohen; Andre Luis Branco de Barros; Armando Silva-Cunha (MDPI AG, 2022)
The eye is an organ with limited drug access due to its anatomical and physiological barriers, and the usual forms of ocular administration are limited in terms of drug penetration, residence time, and bioavailability, as well as low patient compliance. Hence, therapeutic innovations in new drug delivery systems (DDS) have been widely explored since they show numerous advantages over conventional methods, besides delivering the content to the eye without interfering with its normal functioning. Polymers are usually used in DDS and many of them are applicable to ophthalmic use, especially biodegradable ones. Even so, it can be a hard task to find a singular polymer with all the desirable properties to deliver the best performance, and combining two or more polymers in a blend has proven to be more convenient, efficient, and cost-effective. This review was carried out to assess the use of polymer blends as DDS. The search conducted in the databases of Pubmed and Scopus for specific terms revealed that although the physical combination of polymers is largely applied, the term polymer blend still has low compliance.